Business and Product Legality Assistance In Efforts to Improve Branding Quality Jamur Paimo Farm Production House in Ngadirejo Village: Pendampingan Legalitas Usaha dan Produk Dalam Upaya Peningkatan Kualitas Branding Rumah Produksi Jamur Paimo Farm di Kelurahan Ngadirejo - Siti Nurhaliza; Rusdi Hidayat Nugroho (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
MSMEs play an important role in economic growth which has a direct impact on regional economic development. In Ngadirejo Village, Kepanjenkidul District, Blitar City, there is the UMKM "Paimo Farm" which is a production house for oyster mushrooms. The business development implemented is classified as standard so that the existence of the product is little known. This activity aims to enable the MSME "Paimo Farm" to develop into a bigger business and be widely known outside the city by improving the quality of branding. Implementation of activities uses the assistance’s method. Data collection uses interviews and observations. The activity stages include assistance related to business legality, product branding, digital marketing, creating new innovations, developing product packaging, and making product photos. The results of the activity are the issuance of a business registration number (NIB), product innovation and branding.